Binomial sampling of Paraleyrodes Quaintance pos. bondari (Hemiptera: Aleyrodidae) in Persea americana Mill. (2016)
Fresno (Tolima), in Colombia, is a notable avocado producer, with 36% of the national production. In this paper, two sampling methods are presented to assess natural populations of Paraleyrodes Quaintance pos. bondari attacking avocado trees of Hass and Lorena cultivars under field conditions. The presence/absence of whitefly nymph colonies on 30 leaves located at the high, medium and low strata per host plant from both cultivars was evaluated. Visual estimations were performed to count the number of whitefly nymphs on 1.25 cm2 of five leaves/bud in low and medium strata per tree to evaluate the spatial distribution of whitefly population in accordance to Poisson distribution, Negative Binomial distribution and b parameter of Law of Taylor. Significant differences in percentages of infestation (P≤0.03) from leaves that belonged to the low avocado tree strata were found between the Lorena (31.88±1.2%) and Hass (15.64±1.8%) cultivars. Natural populations of P. pos. bondari were located on the abaxial leaf side, showing an aggregate distribution in avocado tree from orchards located at different altitudes. Our findings recommend entomological surveillance for Paraleyrodes sp. pos. bondari in Fresno (Tolima), sampling four branches from the medium and low avocado tree strata through inspection of five buds/branches/tree throughout each branch with the presence/absence method to count whitefly nymph colonies on the abaxial side of pre-basal leaves. In total, the sampling involved five leaves/branch (20 leaves/strata or 40 leaves/tree) on 13 avocado trees per hectare.